Papel da neurotransmissão endocanabinóide no córtex insular sob as respostas cardiovasculares e autonômicas desencadeadas pelo estresse agudo por restrição - Godoy, Ana Caroline Ventris (2021)
Acute stress triggered by aversive situations may favor the onset of neuropsychiatric and cardiovascular diseases, generating very high personal, social and economic costs. Therefore, a clear understanding about the mechanisms involved in the physiological responses during stressful situations is necessary. The insular cortex is a brain region directly involved in the control of behavioral and autonomic processes in aversive contexts. The modulation of these processes can be performed through different neurotransmission systems, as well as the endocannabinoid system. This neurotransmission is closely related to the control of autonomic responses in aversive scenarios. However, the relationship of the endocannabinoid system present in the insular cortex in modulating autonomic responses in stressful situations has not yet been investigated. The aim of this study was to verify the role of endocannabinoid neurotransmission in the insular cortex under cardiovascular responses and tail temperature during acute restraint stress. To this end, guide cannulae were implanted bilaterally, directed to the insular cortex of male Wistar rats for microinjection of the CB1 receptor antagonist (AM251, dose 0, 1 nmol/100nL) and TRPV1 receptors (capsazepine, dose of 15 nmol/100nL) and for the microinjection of the FAAH (URB597, dose of 0.01 nmol/100nL) and MAGL (JZL184, dose of 5 nmol/100nL) enzyme inhibitors. In addition, a polyethylene catheter was implanted in the femoral artery of each animal for measurements of blood pressure (BP) and heart rate (HR). On the day of the experiment, each animal received a bilateral microinjection of the specified drug and 10 minutes later, was placed in a restriction tube and then BP and HR were recorded for 30 minutes. The tail temperature of the animals was recorded, by capturing thermographic images, before drug microinjection, after microinjection, and during the restriction period. The results of this study showed that the use of TRPV1 receptor antagonist was able to provoke the increase of pressure and tachycardic response evoked by acute stress, while the increase of 2-AG, stimulated by MAGL enzyme inhibitor, caused attenuation of pressure and tachycardic responses during aversive stimulus. The FAAH enzyme inhibitor and CB1 receptor blockade were not able to modify cardiovascular responses during acute stress. No treatment used was able to cause significant changes in caudal skin temperature. Our findings suggest that endocannabinoid neurotransmission in the insular cortex modulates pressure and tachycardia responses in an inhibitory manner by means of the endogenous cannabinoid 2-AG, independent of CB1 receptor activation, during acute restriction stress. TRPV1 receptors also play an inhibitory role on the increase in MAP and HR during acute stress, independent of anandamide.